William Lair Hill, Ballinger's Annotated Codes and Statutes of Washington, Showing All Statutes in Force, Including the Session Laws of 1897, at 1956 (Vol. 2, 1897) - (:unkn) unknown (My University, 1881)
Prohibited exhibiting a dangerous weapon in a manner likely to cause terror. Punishable by fine up to $25.
Keywords: BRANDISHING; GOING ARMED